Exploring risky health behaviors and vulnerability to sexually transmitted diseases among transnational undocumented labor migrants from Bangladesh: a qualitative study - Md. Salman Sohel; Md. Khaled Sifullah; Babul Hossain; Md. Fouad Hossain Sarker; Noshin Tasnim Zaman; Md. Obaidullah (BMC, 2024)
Abstract Background In Bangladesh, remittances constitute a substantial portion of the country's foreign exchange earnings and serve as a primary source of income. However, a considerable number of Bangladeshi citizens reside overseas without proper documentation, exposing them to significant challenges such as limited access to healthcare and socioeconomic opportunities. Moreover, their irregular migration status often results in engaging in risky health behaviors that further exacerbate their vulnerability. Hence, this study aimed to investigate the risky health behavior and HIV/STI susceptibility of Bangladeshi irregular international migrants residing across the globe with undocumented status. Methods Using a qualitative Interpretative Phenomenological Approach (IPA), 25 illegal migrants were interviewed who are currently living illegally or returned to their home country. The author used a thematic approach to code and analyze the data, combining an integrated data-driven inductive approach with a deductive approach. Concurrent processing and coding were facilitated by employing the Granheim model in data analysis. Results The study identified four risky health behaviors among irregular Bangladeshi migrants: hazardous living conditions, risky jobs, suicidal ideation, and tobacco consumption. Additionally, the authors found some HIV/STI risk behavior among them including engaging in unprotected sex, consuming alcohol and drugs during sexual activity, and having limited access to medical facilities. Conclusions The findings of this study can be used by health professional, governments, policymakers, NGOs, and concerned agencies to develop welfare strategies and initiatives for vulnerable undocumented migrant workers.